EGFR inhibitors in the treatment of colorectal cancer - M. В. Zabelin; A. D. Kaprin; A. A. Kostin; E. V. Gameeva; S. E. Varlamova (Исследования и практика в медицине)
This ar cle discusses the use of EGFR inhibitors in the treatment of pa ents with colorectal cancer. The mechanisms of their ac on, speciﬁ c manifesta ons of toxicity are considered. A review of current literature data on the use of both approved for clinical use (cetuximab, panitumumab) and an -EGFR an bodies at the stage of clinical trials is presented. EGFR inhibitors are one of the main groups of targeted drugs used to treat pa ents with colorectal cancer. The correla on between toxicity and eﬃ  cacy of these drugs is discussed separately. The scope of their applica on is limited to the treatment of disseminated forms of the disease, but in the future the number of available an -EGFR an bodies may grow, the possibility of their use in new condi ons, including in the framework of chemoradiotherapy.